Leibniz’s Metaphysics of Nature - Rescher, N. author. aut Link
XIV, 128 p.
Keywords: The essays included in this volume are a mixture of old and new. Three of them make their first appearance in print on this occa sion (Nos III, IV, and V). The remaining four are based upon materials previously published in learned journals or anthologies. (However, these previously published papers have been revised and, generally, expanded for inclusion here.) Detailed acknowl edgement of prior publications is made in the notes to the relevant articles. I am grateful to the editors of these several publications for their kind permission to use this material. I am grateful to an anonymous reader for the Western Ontario Series for some useful corrigenda. And I should like to thank John Horty and Lily Knezevich for their help in seeing this material through the press. NICHOLAS RESCHER Pittsburgh, Pennsylvania May, 1980 xi INTRODUCTION The unifying theme of these essays is their concern with Leibniz's metaphysics of nature. In particular, they revolve about his cos mology of creation and his conception of the real world as one among infinitely many equipossible alternatives.